Use of a serious game in teaching bovine veterinarians clinical communication skills: a pilot study: Presenter(s): Linda Dorrestein, University of Calgary, Faculty of Veterinary Medicine, Canada. (April 2023) - Jansen, Jolanda; Plagis, Tessa; Ritter, Caroline; Barkema, Herman
Abstract : Background: Effective communication can aid bovine veterinarians in improving client relationships in herd health consultancy, improving client satisfaction, adherence to veterinary advice and patient welfare and health. Communication skills are often taught using traditional role-play training, which has limitations, e.g., time constraints, assessments and cost. The Veterinary DialogueTrainer (VDT) is a new tool mitigating these barriers. It is a serious game platform using 'digital role-play' with avatars, developed to enhance and assess learning outcomes, improve use of learned skills, and increase cost-effectiveness of communication training. The objective of this pilot study was to determine suitability and applicability for using the VDT. Methods: Twenty-four Finnish bovine veterinarians participated in a communication training using the VDT for training and assessment. After playing the simulation participants received scores and feedback on selected conversation options. VDT scores measure multiple aspects of communication on a 0-100% scale, based on motivational interviewing methodology and Calgary-Cambridge guidelines. Participants completed the provided simulation at least twice. Findings: Mean (±SD) number of attempts participants played the scenario was 4.1 (±2.6), with highest total score reached after a mean of 3.7 (±2.0) attempts. All participants scored<50% at the first attempt of playing the scenario, whereas most participants (n=22) increased their initial score at the second attempt. Mean score increased from 15% (±14%) to 43% (±29%) (paired T-test, p<0.001) and the majority (n=17) of participants was able to reach a score>80% after 4.0 (±1.6) attempts. Discussion: Communication skills scores increased when using the VDT. Whether increased communication skills measured through VDT will improve communication skills in practice is subject of further study. However, based on these results there is likely a benefit of using the VDT in teaching and monitoring veterinary communication competencies and preparing for offline role-plays and real-life conversations in veterinary practice.